The emergence of Pax7-expressing muscle stem cells during vertebrate head muscle development - Nogueira, Julia Meireles; Hawrot, Katarzyna; Sharpe, Colin; Noble, Anna; Wood, William M.; Jorge, Erika C.; Goldhamer, David J.; Kardon, Gabrielle; Dietrich, Susanne (Frontiers in Aging Neuroscience, 2015)
Pax7 expressing muscle stem cells accompany all skeletal muscles in the body and in healthy individuals, efficiently repair muscle after injury. Currently, the in vitro manipulation and culture of these cells is still in its infancy, yet muscle stem cells may be the most promising route towards the therapy of muscle diseases such as muscular dystrophies. It is often overlooked that muscular dystrophies affect head and body skeletal muscle differently. Moreover, these muscles develop differently. Specifically, head muscle and its stem cells develop from the non-somitic head mesoderm which also has cardiac competence. To which extent head muscle stem cells retain properties of the early head mesoderm and might even be able to switch between a skeletal muscle and cardiac fate is not known. This is due to the fact that the timing and mechanisms underlying head muscle stem cell development are still obscure. Consequently, it is not clear at which time point one should compare the properties of head mesodermal cells and head muscle stem cells. To shed light on this, we traced the emergence of head muscle stem cells in the key vertebrate models for myogenesis, chicken, mouse, frog and zebrafish, using Pax7 as key marker. Our study reveals a common theme of head muscle stem cell development that is quite different from the trunk. Unlike trunk muscle stem cells, head muscle stem cells do not have a previous history of Pax7 expression, instead Pax7 expression emerges de-novo. The cells develop late, and well after the head mesoderm has committed to myogenesis. We propose that this unique mechanism of muscle stem cell development is a legacy of the evolutionary history of the chordate head mesoderm.